The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1080/10408398.2010.527023
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Deficiency and Taste Perception in the Elderly

Abstract: Taste, one of the major senses in humans, is the ability to detect the flavor of substances such as food, certain minerals, and poisons. Taste distortions in human beings have been attributed to various physiological and environmental factors including aging and disease conditions. Given the fact that taste is one of the most important factors in food preference, selection, and consumption, the decreased appetite in the elderly, probably due to disease conditions, may lead to dietary restrictions that could ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 37 publications
0
14
0
1
Order By: Relevance
“…It also greatly influences dietary behavior, nutrition and systemic health [26,27]. As about 6.3-20.9% of students had hyposensitivity in this study, more detailed investigation of this problem would be necessary to improve their oral as well as general health.…”
Section: Discussionmentioning
confidence: 97%
“…It also greatly influences dietary behavior, nutrition and systemic health [26,27]. As about 6.3-20.9% of students had hyposensitivity in this study, more detailed investigation of this problem would be necessary to improve their oral as well as general health.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, it has been reported that zinc deficiency is seen in CKD patients and that heavy metal deficiency including zinc deficiency is one of the causes of Erythropoietin-resistant anemia [71]. Moreover, zinc deficiency is known to affect taste that is one of the most important factors in food choice, selection and consumption and it can affect appetite leading to dietary restrictions that could negatively impact nutritional and health status [72]. Hence, iron status, VitB12 zinc levels should be monitored in CKD patients in general and in particular in the elderly and in those following a vegan or very low protein diet for a long time.…”
Section: Discussionmentioning
confidence: 99%
“…Like magnesium, zinc serves as a co-factor to a number of critical enzymes. It is essential for immune function, healthy skin, protein and DNA synthesis and sensory organs [37].…”
Section: Discussionmentioning
confidence: 99%